Acceptability Testing of Moringa-Enriched Corn Porridge as a Local Food-Based Nutritional Intervention for Stunting Prevention in Children Under Five - Heni Aryani; Dea Zara Avila; Alkhair Alkhair; Aris Irwansyah (MESINA (Medical Scientific Journal), 2026)
Indonesia. One of the strategies to prevent stunting is the utilization of nutrient-rich local foods as supplementary feeding for children under five. Corn is an abundant local commodity in Woha District, Bima Regency, and has the potential to be developed into a nutritious food product through the addition of Moringa oleifera leaves, which are rich in protein, vitamins, and minerals. The success of such food products depends not only on their nutritional value but also on their sensory acceptability. Objective: This study aims to determine the acceptability of corn-egg porridge as an effort to utilize local food resources in stunting prevention within the working area of Woha Community Health Center. Methods: This study aims to determine the acceptability of corn-egg porridge as an effort to utilize local food resources in stunting prevention within the working area of Woha Community Health Center. This study is expected to produce a corn-egg porridge formulation with a high level of acceptance based on organoleptic characteristics. The resulting product has the potential to serve as a nutritious, affordable, and locally based supplementary food alternative that can be implemented in stunting prevention programs for children under five years of age.Keywords: stunting, corn porridge, Moringa oleifera, acceptability, local food, hedonic test.